The impact of pandemic Covid-19 to the women porter in Beringharjo Market / Fernando Leonarde and Harsono Dwi - Leonarde, Fernando; Dwi, Harsono (2021)
The COVID-19 pandemic that occurred in various countries, including Indonesia, had a severe impact on health and multiple sectors. One of the most affected is the informal sector. As Neil Adger said, casual workers are vulnerable because they cannot adapt to change (Adger, 2003). Based on the BPS (Central Bureau of Statistic) report informal workers in Indonesia dominate the workforce, about 59.62% (Badan Pusat Statistik, 2021). This has the potential to provide social problems, such as poverty. One of the informal workers suffering from the pandemic is woman porters at Beringharjo Market. During the pandemic, the income of woman porters has decreased significantly. This is because the government's policies reduce the mobility of the people.